The Influence of Peers’ Bullying Behavior on Students’ Emotional Intelligence at Secondary School Level - Saira; Iqbal, Zafar; Masood, Muhammad (Annals of Human and Social Sciences, 2023)
The main theme of the study was to assess “the influence of peers’ bullying behavior on students’ emotional intelligence at secondary school level”. Major objectives of the study were to determine bullying behavior and the emotional-Intelligence among students, to find out the influence of bullying behavior on emotional intelligence among secondary school students. The study was causal comparative in nature. All the students studying in grade 9th of public sectors schools in Tehsil Gujrat were the population of this study. Proportionate Stratified random sampling was used to determine the sample of the study. In this study adapted questionnaires, Bullying Behaviour Scale (BBS) and Emotional-Intelligence Scale (EIS) were used for the collection of data. Collected data were analyzed using descriptive statistics (Frequency, Mean, standard Deviation etc.) as well as inferential statistics (One-way ANOVA). Results of the study concluded that majority of students had low bullying behaviour level as well as the majority of students had moderate level of emotional intelligence schools at secondary level, there was a significant difference among the dissimilar bullying behaviour levels of students on emotional intelligence. On the basis of conclusions, it was recommended that bullying is a phenomenon that is causing to increase concern among students, parents, teachers and head teachers. As a result, academic authorities may develop programs to confront this phenomenon of violence in schools.